Among Culture, Nature and Supernatural. Soundscapes of Sainte-Marie, Madagascar - Kopaniecki, Jakub (Interdisciplinary Studies in Musicology, 2026)
This article explores the soundscapes of Île de Sainte-Marie (Nosy Boraha), an island off the northeastern coast of Madagascar, by combining ethnographic fieldwork with perspectives from sound studies and postcolonial theory. While the research so far has focused on the sonic characteristics of Madagascar’s forests, this article investigates everyday urban, rural, ritual, and natural sound environments. Drawing on field recordings, participant observation, and interviews conducted during a 2024 ethnomusicological expedition, I analyse how sound mediates space, shapes identity, and reflects broader social dynamics. Through the lens of acoustemology and soundscape theory, I argue that sound in Sainte-Marie Island is not merely a backdrop but a cultural force – one that negotiates memory, community, and belonging in a postcolonial context.